A novel duplex SYBR Green real-time PCR with melting curve analysis method for beef adulteration detection. (15th February 2021) - Li, Jiapeng; Wei, Yixuan; Li, Jinchun; Liu, Ruixi; Xu, Suigen; Xiong, Suyue; Guo, Ya; Qiao, Xiaoling; Wang, Shouwei
Highlights: A duplex qPCR assay with melting curve analysis to test cattle was developed. Adulteration was judged by bovine peak, intermediate peak and universal peak. Bovine semi-quantification was calculated by peak area ratio. Target identification with non-target screening raised information density. This method tested efficiently and easily with good accuracy and low cost. Abstract: An efficient and reliable duplex SYBR Green real-time quantitative PCR (qPCR) method for beef products adulteration detection was developed based on bovine specific and vertebrate universal primers. By analyzing the numbers, positions (Tm value) of melting curve peaks of the duplex PCR products, we simultaneously identified bovine and preliminary screened non-bovine in samples, and also semi-quantified the bovine percentage according to the area ratios of peaks. All of these were necessary for adulteration determination. The specific and universal primers were designed based on mitochondrial genes ND4 and 16S rRNA respectively, their amplicons Tm values were 72.6 ± 0.5 °C and 79–81 °C. There might be some other peaks at 74–78 °C and above 81 °C if non-bovine components existed. The limit of detection was 1 pg for bovine DNA, and 1 – 30 pg for non-bovine DNA based on different species.